2021
DOI: 10.1002/jia2.25694
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of assumptions underlying respondent‐driven sampling and the social contexts of sexual and gender minority youth participating in HIV clinical trials in the United States

Abstract: Introduction: Respondent-driven sampling (RDS) has been an effective sampling strategy for HIV research in many settings, but has had limited success among some youth in the United States. We evaluated a modified RDS approach for sampling Black and Latinx sexual and gender minority youth (BLSGMY) and explored how lived experiences and social contexts of BLSGMY youth may impact traditional RDS assumptions. Methods: RDS was implemented in three US cities, Baltimore, Philadelphia and Washington DC, to engage BLSG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Our target population of TSMSM is young and socially marginalized. Other studies have shown that, to varying degrees, RDS is an appropriate and acceptable strategy for recruiting university students [ 31 ]; sexual and gender minority youth, including young MSM [ 32 ]; and young adult non-medical users of pharmaceutical opioids [ 33 ] for research. However, other studies have found that RDS may be an inappropriate strategy for recruiting socially marginalized populations, such as urban young MSM [ 34 ] and young illicit drug users [ 35 ], mainly due to members of the target populations having small network sizes and insufficient ties within their networks, resulting in the inability to sustain recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Our target population of TSMSM is young and socially marginalized. Other studies have shown that, to varying degrees, RDS is an appropriate and acceptable strategy for recruiting university students [ 31 ]; sexual and gender minority youth, including young MSM [ 32 ]; and young adult non-medical users of pharmaceutical opioids [ 33 ] for research. However, other studies have found that RDS may be an inappropriate strategy for recruiting socially marginalized populations, such as urban young MSM [ 34 ] and young illicit drug users [ 35 ], mainly due to members of the target populations having small network sizes and insufficient ties within their networks, resulting in the inability to sustain recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Our target population of TSMSM was young and socially marginalized. Other studies have shown that, to varying degrees, RDS is an appropriate and acceptable strategy for recruiting university students (31), sexual and gender minority youth, including young MSM (32), and young adult non-medical users of pharmaceutical opioids(33) into research. However, other studies have found that RDS may be an inappropriate strategy for recruiting socially marginalized populations such as urban young MSM (34) and young illicit drug users (35), mainly due to members of the target populations having small network sizes and insufficient ties within their networks, thus the inability to sustain recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Where researchers have evaluated RDS methodology among GBM, many have linked sociodemographic characteristics and recruitment productivity [9][10][11]. Wirtz et al (2021) evaluated the use of a modified RDS approach to explore RDS-related challenges when used as a recruitment strategy among young GBM. The authors found that targeted seed recruitment from clinical samples resulted in enrolled participants who reported stable housing, GBM who are living with HIV, and GBM who report PrEP use, while online seeds were more likely to report Latinx ethnicity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Wirtz et al (2021) evaluated the use of a modified RDS approach to explore RDS-related challenges when used as a recruitment strategy among young GBM. The authors found that targeted seed recruitment from clinical samples resulted in enrolled participants who reported stable housing, GBM who are living with HIV, and GBM who report PrEP use, while online seeds were more likely to report Latinx ethnicity [12]. The authors also utilized qualitative interviews and found small social network sizes, limited targeted recruitment referrals and experiences of marginalization, stigma and isolation were barriers to RDS recruitment among young GBM [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation